Triglycerides are a predictive factor for arterial stiffness: a community-based 4.8-year prospective study - Wang, Xiaona; Ye, Ping; Cao, Ruihua; Yang, Xu; Xiao, Wenkai; Zhang, Yun; Bai, Yongyi; Wu, Hongmei (Lipids in health and disease, 2016)
Epidemiological studies have disclosed an independent effect of triglycerides on coronary heart disease despite achievement of low-density lipoprotein cholesterol goals with statin therapy. Arterial stiffness has been increasingly recognized as a strong predictor of cardiovascular disease and atherosclerotic disease. The association between triglycerides and arterial stiffness is not well characterized. We aimed to determine the relationship between triglycerides and arterial stiffness in a community-based longitudinal sample from Beijing, China. We related levels of plasma TGs to measures of arterial stiffness (carotid-femoral pulse wave velocity [PWV] and carotid-radial PWV) in 1447 subjects (mean age, 61.3 years) from a community-based population in Beijing, China. After a median follow-up interval of 4.8 years, multiple linear regression analysis revealed that TGs were independently associated with carotid-femoral PWV (β = 0.747, P < 0.001) and carotid-radial PWV (β = 0.367, P = 0.001). In the group older than 65 years, the association between baseline TG levels and follow-up carotid-femoral PWV (β = 1.094, P = 0.001) and carotid-radial PWV (β = 0.524, P = 0.002) were strengthened. In forward stepwise multivariate logistic regression analysis, every SD increase in TGδ was associated with a 1.296-increased likelihood of the presence of carotid-femoral PWVδII (OR [per SD increase in TGδ]: 1.296; 95% CI: 1.064 ~ 1.580; P = 0.010) in Model 2, whereas the relationship between TGδ and carotid-radial PWVδII disappeared. In addition, the relationship was strengthened between TGδ and the presence of carotid-femoral PWVδII (OR 1.526, 95% CI: 1.088-2.141, P = 0.014) in the group older than 65 years but not carotid-radial PWVδII. No association was noted in subjects younger than 65 years. Lower triglyceride levels were significantly associated with decreases in carotid-femoral PWV, indicating that achieving low TG levels may be an additional therapeutic consideration in subjects with atherosclerotic disease.